A review on Bruton's Tyrosine Kinase inhibitors to outline the scopes of further advancements in the treatment of cancer - Khan, Muidul Hasan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.